2022
DOI: 10.1111/camh.12543
|View full text |Cite
|
Sign up to set email alerts
|

Review: School‐based interventions to improve mental health literacy and reduce mental health stigma – a systematic review

Abstract: Background: The steadily increasing prevalence of mental disorders in children and adolescents presents itself as a public health challenge, especially given the health, social and economic burden of mental disorders. School-based interventions aimed at improving mental health literacy and reducing mental health stigma have the potential to prevent mental disorders and promote mental well-being, thus reducing the burden of mental disorders. This review identified and synthesised evidence on the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 62 publications
2
35
0
1
Order By: Relevance
“…In the context of limited capacity in and access to child and adolescent mental health services (CAMHS), school-based mental wellbeing promotion initiatives have burgeoned, and, in England, become a mandatory part of curricula [7,8]. Research outcomes are mixed, with the best evidence for cognitive behavioural approaches, delivered to whole classes, which facilitates peer support and normalising without labelling vulnerable children [9][10][11]. In practice, outcomes continue to be poor, particularly for more vulnerable children: further development of interventions that are readily implementable longer-term is needed [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of limited capacity in and access to child and adolescent mental health services (CAMHS), school-based mental wellbeing promotion initiatives have burgeoned, and, in England, become a mandatory part of curricula [7,8]. Research outcomes are mixed, with the best evidence for cognitive behavioural approaches, delivered to whole classes, which facilitates peer support and normalising without labelling vulnerable children [9][10][11]. In practice, outcomes continue to be poor, particularly for more vulnerable children: further development of interventions that are readily implementable longer-term is needed [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Scores range from 0 to 20, with lower scores indicating more positive outcomes (clinical cut-off > 9). • M&MF-B 6-item subscale (M&MF items [11][12][13][14][15][16] at 16 weeks. Scores range from 0 to 12, with lower scores indicating more positive outcomes (clinical cut-off > 5).…”
Section: Vulnerable Sub-populationmentioning
confidence: 99%
“…Recent systematic reviews showed that intervention program designs which involved extended contact-time spread over days or weeks and with multiple components (such as survivors lived-experiences and film/ documentaries) had better impact on attitudinal change compared with ultra-short and abridged training programs [ 43 ]. Future depression-literacy programs must be mindful of this design consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Other training programmes, however, have observed sustained poor attitude despite intervention [31,32]. Recent systematic reviews showed that intervention program designs which involved extended contact-time spread over days or weeks and with multiple components (such as survivors lived-experiences and lm/ documentaries) had better impact on attitudinal change compared with ultrashort and abridged training programs [42]. Future depression-literacy programs must be mindful of this design consideration.…”
Section: Discussionmentioning
confidence: 99%